A technological demonstrator for cloud-based performance monitoring and assessment of industrial plants: present architecture and future developments. Issue 2 (2020) - di Capaci, Riccardo Bacci; Scali, Claudio; Vallati, Carlo; Anastasi, Giuseppe
Abstract: This paper presents the actual status and future developments of a technological demonstrator of key enabling technologies of Industry 4.0. The final scope of the project is the realization of a platform where different solutions addressing specific companies needs can be analyzed and their performance compared. Available Industry 4.0 technologies allows the realization of various architectures, even though the most appropriate solution has to be found by the company, accounting for different aspects, as economy, security, specific skills to be maintained or given in outsourcing. The first core of the platform, already working, consists in a Control Loop Performance Monitoring (CLPM) system which operates in cloud as a single module able to supervise routine data coming from different plants. This is an attractive solution for many companies allowing to avoid costs of local installations, linked to monitoring systems, human resources and additional effort for maintenance and upgrading. Some technical details about the application on a pilot-scale plant are given to illustrate the status of the activities. The scope of the project is to add new features to the system as: CLPM extended to plants located in different sites, equipment condition monitoring and environmental data analyses. To this aim, future developments of the platform are discussed in terms of improved technologies, different protocols and architectures.